Size-tailored microwave absorption and reaction activity of Co3O4 nanocatalysts - Nguyen, H.M.; Phan, Chi; Pham, Gia; Asakuma, Y.; Vagnoni, R.; Liu, Shaomin (ELSEVIER SCIENCE INC, 2021)
Microwave (MW)-assisted heterogeneous catalytic chemical reactions have opened advanced routines over the conventional methodology. MW absorption ability of catalyst governed by its particle size is the foremost important factor to be considered before designing catalysts for such MW-based chemistry. Despite considerable interest in applying metallic-based catalysts for MW-assisted reactions, the influences of particle size on catalyst's MW absorption ability and its resultant activity remain elusive. Here, we report an effective approach to tailor the MW absorption ability of Co3O4 catalyst via controlling its particle size during the crystal growth. A developed theoretical model verified that a capping agent could regulate Co3O4 particle size effectively. For the unsupported Co3O4 catalysts, smaller particle size possessed higher MW absorption capacity and thereby delivered higher activity for MW-assisted bi-reforming of methane. High conversion of 63% CH4 and a syngas ratio (H2/CO) of 2.2 was achieved with the smallest Co3O4 particles, at 20 nm. In contrast, the supported Co3O4 samples required larger particles to ensure adequate exposure to the incident MW, which is partially covered by MW-inert support. The results disclose that by tailoring particles size appropriately, metallic-based catalysts can be optimised for MW-based chemical reactions.